Rare Primary Spinal Mesenchymal Chondrosarcoma: A Case Report - Paudel, Sushil; Adhikari, Shirish; Adhikari, Sharad C; Pokharel, Rohit K (Journal of Institute of Medicine Nepal, 2020)
Primary extradural mesenchymal chondrosarcoma (MCS) is a very rare intraspinal tumor. Proper clinical evaluation with magnetic resonance imaging (MRI) followed by biopsy of the mass can confirm the diagnosis. Since MCS has a high tendency of recurrence and metastasis, the prognosis is guarded. We report a 52 years old male with primary extradural MCS in the lumbosacral region (L5-S3). Subtotal excision and biopsy were performed which confirmed the diagnosis. The patient received post excisional radiotherapy but expired after four months. Though rare, this tumor should be kept in differentials which helps in early diagnosis and thus can be treated with radical excision of the mass along with postoperative radiotherapy.